2002
DOI: 10.1088/0953-8984/14/44/304
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study on pressure-induced charge delocalization in Cs2TCNQ3

Abstract: Pressure dependence of several molecular vibration modes in Cs 2 TCNQ 3 has been observed through infrared absorption measurements. The behaviour of the C-CN and C-H stretching modes suggests that a phase transition takes place at around 3.6 GPa. The π * -electrons, which are localized on TCNQ − molecules in the low-pressure phase, are delocalized significantly in the high-pressure phase. However, the radical-like and neutral-like molecules still coexist in the highpressure phase indicating that the electrons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The situation of the dimer-monomer transition in the spin-Pierls system K-TCNQ and Rb-TCNQ [16], as well as the slipped-eclipsed dimer transition in (NMe 4 ) 2 TCNQ 3 [17], for example, can be revealed very well by infrared spectroscopy. Our previous work on the insulator to metal transition in the present substance explained above has also demonstrated that both information on the electronic distribution and crystal structure can be obtained at the same time by this method [12]. Furthermore, as mentioned previously, the effect of magnetic field cannot be detected by X-ray diffraction, but very well observed by infrared spectroscopy [1].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…The situation of the dimer-monomer transition in the spin-Pierls system K-TCNQ and Rb-TCNQ [16], as well as the slipped-eclipsed dimer transition in (NMe 4 ) 2 TCNQ 3 [17], for example, can be revealed very well by infrared spectroscopy. Our previous work on the insulator to metal transition in the present substance explained above has also demonstrated that both information on the electronic distribution and crystal structure can be obtained at the same time by this method [12]. Furthermore, as mentioned previously, the effect of magnetic field cannot be detected by X-ray diffraction, but very well observed by infrared spectroscopy [1].…”
Section: Introductionsupporting
confidence: 65%
“…This metal-like state, however, is considered different from that of ordinary metals, since no Drude tail is observed in the high-pressure phase [9]. High-pressure Raman scattering as well as infrared absorption studies have shown that π* electrons of the TCNQ − are significantly delocalized in the high-pressure phase [10,11]. The delocalization, however, is not complete so that the above-mentioned localization character is maintained, and therefore the substance maintains its semiconducting character.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Let the actual valence of A and B molecules be -ρ A and -ρ B , respectively. Then, since the frequency difference ∆ν of a given infrared mode between the radical-like and neutral-like molecules is known to vary nearly linearly to ρ A − ρ B [5], the following relationship is expected to hold to a good approximation at a pressure P:…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of authors' knowledge, none of these complexes has been reported to exhibit such transition. In Cs 2 TCNQ 3 for example, although excess electrons are significantly delocalized at around 3.6 GPa [3], which corresponds to significantly high electrical conductivity compared to its value it ambient pressure [4], the semiconducting character remains up to 8 GPa [5]. Nevertheless, the change in the distribution of electrons along the TCNQ column that is induced by pressure is interesting.…”
Section: Introductionmentioning
confidence: 99%